Private equity funds and hedge funds: a primer - Ann-Kristin Achleitner; Christoph Kaserer (Technische Universität München, Center for Entrepreneurial and Financial Studies (CEFS), 2005)
Private equity funds and hedge funds are both alternative asset classes that are continuously growing in importance. Although they have different focuses, they share some characteristics. First of all, both have or allegedly have a significant impact on the economy as well as the financial system they operate in. Therefore, the question of a potential regulation of both asset classes arises. Due to the lack of sophisticated knowledge about the differences of these asset classes, market players fear that attempts to regulate hedge funds will adversely affect private equity funds. Besides the regulatory issue, there are several other links between these two asset classes that have to be looked at. The relationship between those two asset classes is therefore of general importance. Last months' developments in the hedge fund industry (e.g. rumors about turbulences as well as hedge funds forcing the dismissal of the CEO of Deutsche Börse) have now even led to a broad public debate about private equity and hedge funds. At least in Germany the debate has been partly fueled by the fact that both types of funds are highly funded by institutional investors from abroad. Due to this the debate widened and included criticism on Anglo-Saxon style capitalism as well. In the light of the last German elections, hedge funds and private equity funds have even been compared to locusts, notorious for exhausting whole countries. However, the distinction between hedge funds and private equity funds remains very vague in this discussion, so that deep mistrust is spread among the public opinion against these new, mostly unknown and misunderstood types of investors. For this reason it is important to * discuss the arguments for or against regulation, * look at the major links between the two asset classes, * look at the major differences that exist between the asset classes, and * conceive a set of criteria to clearly distinguish between both types of funds. The purpose of this paper is to comment on possible solutions to the above mentioned tasks. It outlines preliminary thoughts and findings. Further, it comments on the steps that we think should be taken to further enhance perception of private equity funds as opposed to hedge funds from a public as well as a regulatory perspective.
Keywords: G23; G24; G28; 330; Private Equity Funds; Hedge Funds; Hedgefonds; Private Equity; Regulierung; Börsenregulierung; Deutschland